Quantitative evaluation of facial sagging in different body postures using a three‐dimensional imaging technique - Park, June Whan; Lee, Myeongryeol; Kim, Jihyun; Kim, Eunjoo (Journal of cosmetic dermatology, 2021)
Background The possible contribution of head flexion posture while using a smartphone to the formation of “smartphone face,” is an increasing concern. Smartphone face describes the facial changes in a stooped posture receiving more gravitational pull on the jowl area. Aims In this study, we quantified facial sagging in different postural changes using a three‐dimensional imaging technique. Methods Faces of 21 young (30.45 ± 2.81 yo, n = 11) and old (59.50 ± 3.37 yo, n = 10) Korean female subjects were scanned in different body postures including standing, supine, and head flexion (30°, 45°). The landmark displacements and volumetric changes in facial areas were assessed and correlated with skin elasticity. In addition, 22 Korean female subjects (45.45 ± 3.81 yo) were recruited to test the anti‐gravity effect of facial cream A, which was formulated with Stem III complex™, for 8 weeks. Results The landmarks shifted inferior‐laterally with the supine posture, while the upper face shifted more laterally and the lower face shifted more inferiorly. With a head flexion posture, facial sagging occurred mainly toward the anterior direction with more prominent changes in the lower face. The changes were greater in the older group, and skin elasticity exhibited negative correlation with the shifting distances. A significant decrease in facial sagging was noted after an 8‐week treatment of facial cream A. Conclusion The use of a three‐dimensional imaging technique could accurately assess the gravity‐induced facial changes in different postures. The head flexion posture particularly gives more gravitational pull to the lower face, which could contribute to the drooping jawline.